2006
DOI: 10.1111/j.1346-8138.2006.00079.x
|View full text |Cite
|
Sign up to set email alerts
|

Narrow‐band ultraviolet B as monotherapy and in combination with topical calcipotriol in the treatment of vitiligo

Abstract: Vitiligo is a common, idiopathic, acquired, depigmenting disease characterized by loss of normal melanin pigments in the skin. The most interesting treatment methods for extensive vitiligo involve psoralen plus ultraviolet A (PUVA) therapy and ultraviolet (UV)-B phototherapy, particularly narrow-band UV-B. In this randomized and comparative study, we investigated the safety and efficacy of narrow band ultraviolet B as monotherapy and in combination with topical calcipotriol in the treatment of generalized viti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(55 citation statements)
references
References 31 publications
3
50
0
2
Order By: Relevance
“…In our study, the average area of secondary involvement (VASI Score) in patients was lower than the initial average area of involvement, indicating the effectiveness of NBUVB therapy in the treatment of vitiligo, which is consistent with previous studies (2,15).…”
Section: U N C O R R E C T E D P R O O Fsupporting
confidence: 81%
“…In our study, the average area of secondary involvement (VASI Score) in patients was lower than the initial average area of involvement, indicating the effectiveness of NBUVB therapy in the treatment of vitiligo, which is consistent with previous studies (2,15).…”
Section: U N C O R R E C T E D P R O O Fsupporting
confidence: 81%
“…Studies reporting the use of NBUVB monotherapy in vitiligo reported initial repigmentation after 7-16 weeks of treatment in one study [14] and after an average of 34 treatments or 17 weeks of therapy in the other [15]. In studies using NBUVB for the therapy of vitiligo, overall repigmentation rates of 41.6-100% were reported to occur [15,16,17,18,19,20], and only 9% showed more than 75% repigmentation [17]. Although our study is retrospective and did not directly assess the effect of oral MPD mini-pulse therapy in association with NBUVB versus oral MPD mini-pulse therapy alone, the results observed in our series of patients treated with oral MPD mini-pulse therapy in association with NBUVB suggest that the combination of NBUVB and oral MPD mini-pulse therapy may induce repigmentation faster, and in a higher percentage of cases.…”
Section: Discussionmentioning
confidence: 99%
“…There are a number of studies reporting conflicting results on repigmentation [4,5,6,7]. Vitamin D is known to influence melanocyte maturation, differentiation and melanogenesis.…”
Section: Introductionmentioning
confidence: 99%